2014
DOI: 10.1063/1.4898805
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of improved ferroelectric phase stabilization in Nd and Sc co-substituted BiFeO3

Abstract: Polycrystalline BiFeO3 and Bi0.9Nd0.1Fe1-xScxO3 (x = 0, 0.05 and 0.10) multiferroic compounds were prepared using conventional solid-state route. X-ray diffraction studies and Raman measurements indicated that the compounds were crystallized in rhombohedral structure with R3c space group. Weak ferromagnetism was induced due to the suppression of canted spin structure in the substituted compounds. Both remnant magnetization (Mr) and coercive field (Hc) were enhanced in Nd and Sc substituted compounds. Further, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The group theory predicts that there are 13 active Raman modes in the BFO with R3c space group, which can be described as: Γ = 4 A 1 + 9 E . Among them, the low frequency Roman modes (below 170 cm −1 ) are associated with Bi atom, while those at median frequencies (150‐270 cm −1 ) are responsible for Fe atom . At room temperature, the Raman spectrum of the nondoped BFO nanoparticles and the fitted curves is depicted in Figure A.…”
Section: Resultsmentioning
confidence: 99%
“…The group theory predicts that there are 13 active Raman modes in the BFO with R3c space group, which can be described as: Γ = 4 A 1 + 9 E . Among them, the low frequency Roman modes (below 170 cm −1 ) are associated with Bi atom, while those at median frequencies (150‐270 cm −1 ) are responsible for Fe atom . At room temperature, the Raman spectrum of the nondoped BFO nanoparticles and the fitted curves is depicted in Figure A.…”
Section: Resultsmentioning
confidence: 99%
“…In this manner, Rao at el. prepared Nd-Sc co-substituted BFO ceramic and found phase stabilization with remarkably enhanced multiferroic properties [27]. Khomchenko et al studied the Bi 1-x Nd x Fe 1-x Mn x O 3 multiferroic system and revealed structural phase transformation from polar state to non-polar one with increasing 'x', but got enhanced magnetization [28].…”
Section: Introductionmentioning
confidence: 98%
“…It has been observed that the substitution of Sc at the Fe-site of BFO enhances the insulating character by reducing the leakage current. 10,11 Also, it is reported that rare earth substitution at Bi-site enhances the multiferroic properties and reduces the leakage currents. 11,12 In addition to the improved properties, the substitution distorts the crystal structure and transforms to another structure.…”
Section: ••mentioning
confidence: 99%
“…10,11 Also, it is reported that rare earth substitution at Bi-site enhances the multiferroic properties and reduces the leakage currents. 11,12 In addition to the improved properties, the substitution distorts the crystal structure and transforms to another structure. A structural transition from rhombohedral to an orthorhombic structure is observed for 0.10 < x < 0.15 in the Bi 1-x Eu x FeO 3 compound.…”
Section: ••mentioning
confidence: 99%
See 1 more Smart Citation